Review of studies that have used knockout mice to assess normal function of prion protein under immunological or pathophysiological stress. (July 2014) - Onodera, Takashi; Sakudo, Akikazu; Tsubone, Hirokazu; Itohara, Shigeyoshi
Abstract Deletion of cellular isoform of prion protein (PrPC) increases neuronal predisposition to damage by modulating apoptosis and the negative consequences of oxidative stress. In vivo studies have demonstrated that PrPC‐deficient mice are more prone to seizure, depression, and induction of epilepsy and experience extensive cerebral damage following ischemic challenge or viral infection. In addition, adenovirus‐mediated overexpression of PrPC reduces brain damage in rat models of cerebral ischemia. In experimental autoimmune encephalomyelitis, PrPC‐deficient mice reportedly have a more aggressive disease onset and less clinical improvement during the chronic phase than wild‐type mice mice. In mice given oral dextran sulfate, PrPC has a potential protective role against inflammatory bowel disease. PrPC‐deficient mice demonstrate significantly greater increases in blood glucose concentrations after intraperitoneal injection of glucose than wild‐type mice. Further in vivo challenges to PrP gene‐deficient models and conditional knockout models with siRNA and in vivo administration of PrP‐ligating agents may assist in refining knowledge of the lymphoid function of PrPC and predicting the effects of anti‐PrP treatment on the immune system. Together, these findings indicate that PrPC may have multiple neuroprotective and anti‐inflammatory roles, which explains why this protein is so widely expressed.